2012
DOI: 10.1111/j.1439-0329.2012.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosellinia necatrix attack according to soil features in the Mediterranean environment

Abstract: A study was carried out on Rosellinia necatrix attack on young woody plants, as possibly affected by selected soil features under three water regimes. Six different soil systems representing five agro-environments and one forest in the Puglia Region (southern Italy -Mediterranean climate) were compared. R. necatrix attack on sweet cherry trees was simulated using artificial inoculum and saplings of Prunus mahaleb, the most widely used rootstock of sweet and sour cherries, monitored during the spring period. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…‛Favolosa’ is planted throughout Apulia due to its resistance to OQDS, which destroyed several olive groves (Boscia et al, 2017 ). At the same time D. necatrix affects several tree species in Apulia (Carlucci et al, 2013b ) and in this work we clearly showed that ‛Favolosa’ can succumb to D. necatrix, especially in the phase of arboretum constitution. Finding an additional effective control measure is thus particularly important.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…‛Favolosa’ is planted throughout Apulia due to its resistance to OQDS, which destroyed several olive groves (Boscia et al, 2017 ). At the same time D. necatrix affects several tree species in Apulia (Carlucci et al, 2013b ) and in this work we clearly showed that ‛Favolosa’ can succumb to D. necatrix, especially in the phase of arboretum constitution. Finding an additional effective control measure is thus particularly important.…”
Section: Discussionsupporting
confidence: 66%
“…It is present in five continents in temperate, tropical and subtropical zones (Pérez-Jiménez, 2006 ; Schena et al, 2008 ; Pliego et al, 2012 ; Pasini et al, 2016 ). Dematophora necatrix has been isolated from roots of olive trees in France (Guillaumin et al, 1982 ), Portugal (Roca et al, 2016 ), and Spain (Figueres & Grouard, 2001 ), and it also infects olive trees in Italy (Faretra & Frisullo, 2002 ; Schena et al, 2008 ; Carlucci et al, 2013b ).…”
Section: Discussionmentioning
confidence: 99%
“…was not influenced by TT-OMWW, while on HPH-OMWW, τ increased from 2.93 ± 0.17 days (5%) to 15.95 ± 0.01 days (15%). S. rolfsii and R. necatrix are severe soilborne fungal pathogens of horticultural crops and fruit trees, respectively, as reported by Lops et al ( 2008 ) and Carlucci et al ( 2013 ), and their growth was inhibited by 10 and 15% TT-OMWW.…”
Section: Resultsmentioning
confidence: 55%
“…Athelia rolfsii (Ar) and Rosellinia necatrix (Rx) are known as two severe soilborne fungal pathogens of horticultural crops [22] and fruit trees [23]. The first was affected by both acids although in a different way, since it experienced complete inhibition in the presence of cinnamic acid, while τ increased from 3.00 to 6.31 days in the presence of vanillic acid.…”
Section: Growth Kinetic On Solid Media Containing Cinnamic or Vanillimentioning
confidence: 99%